Application of transfer relations to structural analysis of arch bridges - Zhang, Jiao-Long; Hellmich, Christian; Mang, Herbert A.; Yuan, Yong; Pichler, Bernhard (Computer Assisted Methods in Engineering and Science, 2017)
Transfer relations, representing analytical solutions of the linear theory of slender circular arches, have facilitated structural analysis of segmented tunnel linings. This is the motivation to apply such relations to two examples concerning circular arch bridges, carrying the bridge deck by means of equally spaced hangers. At first, the number of hangers is optimized in order to minimize the maximum bending moment of the arch, thus allowing the latter to come as close as possible to the desired thrust-line behavior. Secondly, analytical solutions for a “uniform temperature change” are derived. They are used to show that a temperature increase by 30 K results only in minor redistributions of the inner forces but in significant additional deflections. The two examples have shown that the transfer relations are useful for structural analysis of circular arch bridges, because they reduce the complexity of the analysis to that of structural systems consisting of straight beams.